The tongue and floor of the mouth cancer – diagnostics and advances in treatment - Kruk-Zagajewska, Aleksandra; Wierzbicka, Małgorzata (Contemporary Oncology/Współczesna Onkologia, 2003)
In the recent years the occurrence of tongue and floor of the mouth malignancies has increased. This group of patients comprises mainly males who abuse alcohol and are heavy smokers. Well known precancerous lesions of the oral cavity include erytroplasia, leucoplakia and subcutaneus fibrosis. The tongue and floor of the mouth cancer is characterised by high dynamics of development and clinical malignancy. The early neck metastases, in numerous cases bilateral, worsen the prognosis. The analysis concerned 123 patients with the tongue and floor of the mouth cancer treated surgically in the ENT Department of Karol Marcinkowski University of Medical Sciences in Poznań in the years 2000–2001. To assess the tumor advancement, apart from clinical examination, percutaneous and endoscopic ultrasonography was used. Nearly 60% of patients were admitted with III and IV stages of tumor advancement. In 55% of patients neck metastases were confirmed. In the majority of cases the squamous cell carcinoma was recognised in the histological assessment. The current trends of treatment depending on the stage of tumor advancement were presented.